Murabahah Financing in Islamic Banks with Fiduciary Collateral Review from the Perspective of Legal Certainty and Utility - Nugraha, Ivan; Imaniyati, Neni Sri; Putra, Panji Adam Agus (Future Science, 2024)
One of the financing contracts offered by Islamic banks is the Murabahah financing contract. The Murabahah financing contract functions to increase the utility of money and capital, as well as the utility of goods. Article 127 of the Compilation of Sharia Economic Law (KHES) allows the seller to request the buyer to provide collateral in the Murabahah contract. Fatwa DSN-MUI No. 03/DSN-MUI/IV/2000 regarding Murabahah permits banks to request collateral from financed customers. This provision aims to ensure that customers are serious about making payments. Based on KHES and the fatwa, banks are allowed to request collateral from customers to protect or ensure that their rights are not violated. In practice, to ensure that customers comply with payments, banks request collateral from customers. This collateral can be movable or immovable property. Collateral in the form of immovable property is called fiduciary collateral. Fiduciary collateral is regulated in Law No. 42 of 1999 concerning Fiduciary Collateral (UUJF). According to Article 5 paragraph 1 of UUJF, the imposition of collateral with fiduciary collateral